Distinct features of the host-parasite interactions between nonadherent and adherent Trichomonas vaginalis isolates. - Hong-Ming Hsu; Yen-Yu Yang; Yu-Hsin Huang; Chien-Hsin Chu; Ting-Jui Tu; Yen-Ting Wu; Chu-Jen Chiang; Shi-Bing Yang; Daniel K Hsu; Fu-Tong Liu; Jung-Hsiang Tai (Public Library of Science (PLoS), 2023)
Cytoadherence of Trichomonas vaginalis to human vaginal epithelial cells (hVECs) was previously shown to involve surface lipoglycans and several reputed adhesins on the parasite. Herein, we report some new observations on the host-parasite interactions of adherent versus nonadherent T. vaginalis isolates to hVECs. The binding of the TH17 adherent isolate to hVECs exhibited an initial discrete phase followed by an aggregation phase inhibited by lactose. T. vaginalis infection immediately induced surface expression of galectin-1 and -3, with extracellular amounts in the spent medium initially decreasing and then increasing thereafter over the next 60 min. Extracellular galectin-1 and -3 were detected on the parasite surface but only the TH17 adherent isolate could uptake galectin-3 via the lysosomes. Only the adherent isolate could morphologically transform from the round-up flagellate with numerous transient protrusions into a flat amoeboid form on contact with the solid surface. Cytochalasin D challenge revealed that actin organization was essential to parasite morphogenesis and cytoadherence. Real-time microscopy showed that parasite exploring and anchoring on hVECs via the axostyle may be required for initial cytoadherence. Together, the parasite cytoskeleton behaviors may collaborate with cell surface adhesion molecules for cytoadherence. The nonadherent isolate migrated faster than the adherent isolate, with motility transiently increasing in the presence of hVECs. Meanwhile, differential histone acetylation was detected between the two isolates. Also, TH17 without Mycoplasma symbiosis suggests that symbiont might not determine TH17 innate cytoadherence. Our findings regarding distinctive host-parasite interactions of the isolates may provide novel insights into T. vaginalis infection.